Sosialisasi Untuk Meningkatkan Kedipsilinan Siswa Dalam Masuk Sekolah di SMK Muhammadiyah X Banjarmasin: Penelitian - Ani Wardah; Aminah; Nurul Auliah; Novi Rahmawanti; Dewi Sa’adah; Laura Sapitri; Amelia Rahmah; Nurhidayah Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Discipline in Islam is extensively explained in the Quran and Hadith. This community service program aims to increase students' awareness and discipline in time management, particularly in reducing lateness to school. This activity involved 25 11th-grade office students. The program consisted of two main sessions: a socialization session and a training session. In the first session, participants were given an understanding of the importance of effective time management, followed by a pre-test to measure initial understanding. The second session covers material on time management from an Islamic perspective, practical techniques for waking up early, and making daily plans using the Time Blocking and To-Do List methods. Evaluation through post-test showed an increase in students' understanding of the importance of time discipline by 124. This indicates an increase in student discipline regarding lateness to school. The results of this activity are expected to reduce student tardiness and help them manage their daily time more structured.